Impacts of environmental factors on zooplankton taxonomic diversity in coastal lagoons in Turkey - Emir Akbulut, Nuray; Tavsanoglu, Ulku Nihan (Tubitak Scientific & Technological Research Council Turkey, 2018)
Lagoons are valuable ecosystems providing various services, such as fishing, recreational activities, and land reclamation, as well as hosting high biodiversity. Although lagoons in Turkey cover a coastal area of more than 36,000 ha, few studies of them have been conducted. Therefore, two lagoons (Dalyan and Arapciftligi) located on the coast of the Sea of Marmara in the Kocacay Delta, which is under intense anthropogenic pressure, were investigated between November 2013 and March 2015 to examine the effects of environmental factors on taxonomic diversity. In addition, ongoing high nutrient flow from the Karacabey region triggers eutrophication in the lagoons, thus causing low water transparency. In both lagoons, the zooplankton assemblages were mainly dominated by cosmopolite and eurytopic taxa. Calanoid copepod Acartia clausi was the dominant species in both lagoons and showed seasonal variation, while no seasonality appeared in nauplii. The high abundance of rotifer species of the genera Keratella and Brachionus reflects the harsh conditions in the lagoons, caused by cultural eutrophication, dystrophy, and salinity increase and also by the temperature-enhanced decrease in zooplankton evenness and richness. Flushing rate, precipitation, high temperature, and salinity influence the species composition, which shifted to a greater dominance by hypoxia/salinity-tolerant zooplankters, resulting in lower species diversity in the lagoons.
Impacts of environmental factors on zooplankton taxonomic diversity in coastal lagoons in Turkey
Keywords: Zooplankton; Lagoon; Species Diversity; Salinity; Mediterranean